Speaking of transparency: Are all Artificial Intelligence (AI) literature reviews in education transparent? (Journal of Applied Learning and Teaching, 2023)
Literature reviews are considered a core research approach in developing new theories and identifying trends and gaps in a given research topic. However, the transparency level of literature reviews might hinder the quality of the obtained findings, thus limiting their implications. As transparency is one of the core elements when implementing Artificial Intelligence (AI), this study assesses the transparency level of literature reviews on AI in education. Specifically, this study used a systematic review to collect and analyze information about reports of methodological decisions and research activities in 61 literature review papers. The obtained findings highlighted that 51.9% of the conducted reviews on AI in education are descriptive. Additionally, the transparency level of the conducted literature reviews was low; 40% of the reviews were in Q1 and 32% in Q2. Particularly, the quality assessment step had the lowest transparency level. The findings of this research can advance the educational technology field by underscoring the methodological gaps when conducting a literature review on AI in education and hence enhance the transparency and trustworthiness of the obtained findings.